#TITLE_ALTERNATIVE# - HARJA (NIM : 12212095), CANDRA
The development strategy of gas reservoir supported by an active bottom-water aquifer is essential and requires complete attention. Water inflow may cease production of gas wells, leaving a significant amount of gas in the reservoir. One of the most promising technique to enhance gas recovery is the co-production technique. This technique includes dual completion with an isolating packer at the bottom completion. The increased recovery is attributed to a reservoir response much similar to a depletion-drive since reservoir pressure is reduced due to water production, therefore more gas is produced by gas expansion. This paper attempts to describe and evaluate potential of associated production technology. Simulation studies were conducted, utilizing numerical simulator to develop the model and investigate recovery optimization by co-production. Sensitivity analyses are carried on define optimum rate for both completions and also the schedule of co-production. It is determined that the water production rate needed to optimize recovery increases over time, and that accelerating production rate causes the optimum co-production rate to increase even faster over time.